Magnetic resonance imaging evaluation of painful knee joint: an experience form a rural medical college of West Bengal, India - Nandy, Debabrata; Sinha, Nirmalya (International Journal of Research in Medical Sciences, 2019)
Background: Painful knee is considered as one of the most common causes of morbidity and disability affecting all age group. It happens due to varied reasons ranged from injury to various disease processes. The present study documented the magnetic resonance imaging (MRI) findings in painful knee. Methods: A hospital based cross-sectional study was conducted among 100 painful knee patients referred to the Radiodiagnosis department of the Midnapore Medical College of West Bengal for evaluation. MRI scans performed using GE 1.5 Tesla MRI scanner. Results were expressed in terms of numbers and proportions. Results: The commonest soft tissue lesion found was meniscal tears which mainly involved posterior horn of the medial meniscus and of grade 2 nature. In case of any injury, vertical meniscal tear was found the commonest type. Tear was found the commonest lesion involved the anterior-cruciate ligament (ACL), mostly acute in nature while partial tear commonly found in posterior-cruciate ligament (PCL). Nearly one-third (30%) had features of bone contusions; mostly tibia followed by lateral femoral condyle. Popliteal cyst was the commonest cystic lesion and was associated with effusions and meniscal tears while patello-femoral compartment mostly involved by the osteo-arthritic process. Conclusions: MRI is an ideal, non-invasive and more precised imaging technique for the radiological evaluate of the painful knee condition for better clinical management.